Effect Of Dried Orange Peels As Feed Replacement And Stocking Density On Broiler Productive Performance - O.H., Zainab; A., Khasraw A.; A.R, Saman (Sulaimani Journal for Pure and Applied Sciences, 2016)
This study was conducted at the poultry farm of Faculty of Agricultural Sciences, University of Sulaimani, in Bakrajo from 8/8/2014 to 1/1/2015. The experiment included managing and treating the birds at the farm to obtain the effect of Dried Orange Peels (DOP) levels on production performance of Ross-308 broilers at the 15- 42 days of age. The experiment was divided into five periods; each period lasted 7 days except fifth period lasted 15- 42 days. The birds were treated with different levels of DOP and different stocking density. The experimental treatments included eight treatments as following: T1: Control Diet + 0% dried orange peel+ normal stocking density (8 birds/m2). T2: CD + 0% dried orange peel+ high stocking density (12 birds/m2). T3: CD + 3% dried orange peel+ normal stocking density. T4: CD + 3% dried orange peel+ high stocking density. T5: CD + 6% dried orange peel+ normal stocking density. T6: CD + 6% dried orange peel+ high stocking density. T7: CD+ 9% dried orange peel+ normal stocking density. T8: CD + 9% dried orange peel+ high stocking density. The results obtained from this study showed that the effect of Dried Orange Peels (DOP) levels and stocking density significantly (P≤0.05) affected feed intake, body weight, body weight gain and feed conversion ratio.
Keywords: Broilers; Dried Orange Peels; Stocking Density